Farm Tourism in the Philippines Amid the Covid-19 Pandemic: Assessment Using the TOWS Analysis Approach - Princess M. Feliciano; Gener T. Cueno; Tania Marie P. Melo (Future Science / FSH-PH Publications, 2025)
This study examines the profiles of Department of Tourism (DOT) – accredited farm tourism owners and their enterprises in Cavite, providing one of the first empirical assessments of the financial and operational impacts of the COVID–19 pandemic on this niche tourism sector. Using interviews with six farm owners and managers, the study analyzed demographic characteristics – sex, age, civil status, educational attainment, and primary occupation – as well as enterprise attributes such as business type, years of operations, farm size, services offered, employee demographics, guest volume, and farm revenue. Descriptive statistics (frequency, mean, and percentage) were used in the analysis. Findings show a balanced gender distribution among owners, most of whom are married, have completed college, and engaged primarily in farming, with an average age of 55. More than half of the enterprises operate as corporations, have been in business for 10 years, and maintain an average farm size of 8 hectares. While pandemic restrictions limited operations to 30 percent capacity, the data reveal an overall increase in average revenue, suggesting adaptive income-generation strategies and resilience within the sector. The positive change can be attributed to a stronger strategic focus on educational tourism services and emerging digital marketing efforts in spite of the industry restrictions.